The Impact Socialization of Fire Disaster Mitigation to Increasing Student’s Knowledge at Muttaqien Junior High School: Dampak Sosialisasi Mitigasi Bencana Kebakaran Terhadap Peningkatan Pengetahuan Siswa di SMP Muttaqien - Setiawan, Cahyadi; Dwi Sukanti Lestariningsih; Elisabeth Nugrahaeni Prananingrum; Muhammad Wahyu Wardana (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
DKI Jakarta was very disaster-prone area, therefore it necessary to strive for strategic steps to protect every citizen with disaster management efforts. Potential disasters in urban areas other than flooding are building and residential fires. This study was aim to determine the impact of fire disaster mitigation socialization on increasing students' knowledge at SMP Muttaqien, South Jakarta. Impact is calculated by knowing the difference in knowledge before and after socialization. The analysis technique used paired sample T-test. The sample was determined using random sampling, with total of 41 respondents. Based on the results of data processing, it was foundthat there was an increase in knowledge on students about fire disaster mitigation. This can be seen through the increased of the student's mean score, from 79.27 to 85.12. So it can be concluded that this socialization activity has a positive impact on increasing students' knowledge in dealing with fire disasters.